Advancing Sports and Exercise via Innovation Proceedings of the 9th Asian South Pacific Association of Sport Psychology International Congress (ASPASP) 2022, Kuching, Malaysia - Kuan, Garry; Chang, Yu-Kai.; Morris, Tony.; Eng Wah, Teo.; Musa, Rabiu Muazu; P. P. Abdul Majeed, Anwar (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book presents the proceedings of the 9th Asian South Pacific Association of Sport Psychology International Congress (ASPASP) 2022, Kuching, Malaysia, which entails the different sporting innovation themes, namely, Applied Sport and Social Psychology, Health and Exercise, Motor Control and Learning, Counselling and Clinical Psychology, Biomechanics, Data Mining and Machine Learning in Sports amongst others. It presents the state-of-the-art technological advancements towards the aforesaid themes and provides a platform to shape the future direction of sport science, specifically in the field sports and exercise psychology. 1.Presents articles from 9th Asian South Pacific Association of Sport Psychology International Congress 2022, Malaysia 2. Brings together academics and industries to present recent findings and innovations in sports and exercise 3. Includes contributions from leading experts in both industry and academia.
Advancing Sports and Exercise via Innovation -- Commitment in Sport from the perspective of Malaysian Adults -- Effectiveness of Brain Breaks -- The Fundamental Motor Skills Performance of Children -- Speed Agility Training Aids Set.
Keywords: Biomedical engineering; Social psychology; Sports sciences; Recreation -- Equipment and supplies; Machine learning; Data mining; Biomedical Engineering and Bioengineering; Social Psychology; Sport Technology; Machine Learning; Data Mining and Knowledge Discovery; Sports Biomechanics